Manual of Clinical Problems in Infectious Diseases, 5th Edition - Gantz, Nelson M.;, Brown, Richard B. Berk, Steven L. Myers, James W. (Lippincott Williams & Wilkins, 2006)
In 1979, at the request of our students and house officers, Drs. Richard Gleckman and Nelson Gantz prepared the first edition of Manual of Clinical Problems in Infectious Disease. At the time, our aim was to provide medical students, house officers, and practitioners with a contemporary approach to selected problems in infectious disease; key annotated references supported in the text. In 1986, with the help of two additional authors, Drs. Richard Brown and Anthony Esposito, the second edition of Manual of Clinical Problems in Infectious Disease was published and covered a list of new subjects. Since that time, numerous infectious agents have been recognized, new concepts have evolved, and new treatments have emerged. For the third edition, to satisfy the contemporary text addressing this information, we prepared a new list of subjects and added Dr. Steven Berk to our team. The fifth edition of Manual of Clinical Problems in Infectious Disease is not simply an updated version of the four earlier books: it re-examines some older material and explores new subjects such as West Nile virus, SARS, and Parvovirus. For this edition, we are pleased to add Dr. James Myers to the team. Every effort has been made to add contemporary references to the text to enhance the accuracy of the manual and to provide a springboard for further reading; many references are annotated. Like the four previous editions, this manual is not meant to be all-inclusive. Numerous major texts that fulfill this mission have already been published. The fifth edition of Manual of Clinical Problems in Infectious Disease represents an attempt to provide contemporary, scientifically accurate, and readable material on selected topics of concern to the practicing physician, house officer, and medical student. All of the editors are clinicians who see patients on a regular basis and have written chapters based on a Ã¢â‚¬Å“real worldÃ¢â‚¬Â approach to patient care while keeping with a scientific basis of management. Chapters have been added, removed, or revised in keeping with changes in infectious disease over the past 6 years. We are proud of our effort and feel that this book will prove valuable to the clinician in the day-to-day management of patients with infectious disease.